What Does it Mean to ‘Belong’?:: A Narrative Literature Review of ‘Belongingness’ Among International Higher Education Students - Mohamad, Dania; Manning, Keenan Daniel (Journal of International Students, 2023)
Following the gradual post-COVID-19 return of international student flows, it is important to examine how higher education institutions and international students are reacting to their new environment and how they relate to each other. Central to this relationship is the concept of ‘belonging’; what it means for international students, as newcomers and temporary residents in their host environment, to feel as if they belong. To address this question, and as a springboard from which further research into the topic can be undertaken, we examined the question of ‘belonging’ within contemporary academic literature. We examined a broad range of literature to determine the key findings, as well as gaps in the implications for theory and practice. Our findings indicate that ‘belonging’ is seldom clearly defined in the scholarly research. We also found that a proactive approach to student integration was the most common thread across the studies examined.